Introduction: historical geographies of internationalism, 1900-1950 - Hodder, Jake; Legg, Stephen; Heffernan, Mike (Elsevier, 2015)
This introduction to a special issue on historical geographies of internationalism begins by situating the essays that follow in relation to the on-going refugee crisis in Europe and beyond. This crisis has revealed, once again, both the challenges and the potential of internationalism as a form political consciousness and the international as a scale of political action. Recent work has sought to re-conceptualise internationalism as the most urgent scale at which governance, political activity and resistance must operate when confronting the larger environmental, economic, and strategic challenges of the twenty-first century. Although geographers have only made a modest contribution to this work, we argue that they have a significant role to play. The essays in this special issue suggest several ways in which a geographical perspective can contribute to rethinking the international: by examining spaces and sites not previously considered in internationalist histories; by considering the relationship between internationalism in the abstract and the geographical and historical specifics of its creation; and by analysing the interlocking of internationalism with other political projects. We identify, towards the end of this essay, seven ways that internationalism might be reconsidered geographically in future research: through its spatialities and temporalities, the role of newly independent states, science and research, identity politics, and with reference to its performative and visual dimensions.